Seasonal Fe Uptake of Young Citrus Trees and Its Contribution to the Development of New Organs - Martínez-Cuenca, Mary-Rus; Martínez-Alcántara, Belén; Millos, Jorge; Legaz, Francisco; Quinones, Ana (MDPI, 2021)
This work quantifies Fe uptake in young citrus trees, its partitioning among plant compartments, and the contribution of the Fe absorbed from fertilizer to the development of new tissues. A soil pot experiment was conducted using 4-year-old clementine trees (Citrus clementina Hort ex Tan), and a dose of 240 mg Fe was applied by labeled fertilizer (92% atom 57Fe excess). Plants were uprooted at five different phenologic states: end of flowering (May 15), end of fruit setting and fruit drop (July 1), two fruit growing moments (August 1 and October 15), and at complete fruit maturity (December 10). The Fe accumulated in the root system exceeded 90% of the total Fe content in the plant. All organs progressively enriched with 57Fe (8.5–15.5% and 7.4–9.9% for young and old organs, respectively). Reproductive ones reached the highest increase (111% between May and October). 57Fe enrichment from woody organs reflects an increasing gradient to sink organs. The root system accumulated 80% of the Fe absorbed from the fertilizer, but the young organs accumulated relatively more Fe uptake during flowering and fruit setting (15.6% and 13.8%, respectively) than old organs (around 9.8%). Although iron derived from fertilizer (Fedff) preferably supplied young organs (16.7–31.0%) against old ones (2.5–14.9%), it only represented between 13.8% and 21.4% of its content. The use efficiency of the applied Fe (FeUE) barely exceeded 15%. The lowest FeUE were found in young and old organs of the aerial part (1.1–1.8% and 0.7–1.2%, respectively). Since the pattern of the seasonal absorption of Fe is similar to the monthly distribution curve of the supplied Fe, it is recommended that the application of Fe chelates in calcareous soils should be performed in a similar way to that proposed in this curve.